Educação matemática : processos interativos em situações de jogo no ensino fundamental - Raupp, Andréa Damasceno (2009)
The worry about the learning of math involves some precautions which are considered by the teacher when drawing up his/her pedagogical proposal, such as: care with the student, with math, with the school and social context. Games play a role in our social context and are coming to occupy a school space, by promoting interaction among the players. The aim of this research is the use of games in the classroom as one of the trends in math education. Due to the importance of critical analysis of the pedagogical action, the choice of the theme is justified in view of the need of the technical-methodological reflection about the practice itself with games. Thus, the main problem is expressed in the following way: What interaction may be provided by games in order to promote learning and development by the students? Thus, the aim of this work is to analyze the interactions in the game situations. Therefore one analyzes episodes which picture moments of the teachinglearning process which have games as a resort. The episodes have been obtained by the teacher from the year 2002 on, and the teaching plans have been drawn up by her. The students who participate in the activities belong to the fourth, fifth and sixth grades of a private high-school in Passo Fundo/RS. Considering the interactive process, mediated by language as a learning determiner, the analysis is conducted on a basis of historic-cultural theory. In this process one stresses aspects such as the importance of creating interaction spaces that promote learning; intervention and dialogue among the students themselves and of the students with the teacher. Besides these, other aspects concerning the shaping of the human being are pointed out, such as trust, cooperation, honesty, respect to established rules and solidarity. As a result of the analysis, one notices the beginning of changes in the teacher s concepts, and the changes that can also be perceived in the activity practice of the game. Among them, the more judicious choice of a game that provides the student especially with the need to argue or to defend his/her point of view and the change concerning the way of interaction at the moment when the teacher starts to question the students about the used procedures during the game by having them reflect about and explain their actions. Based on what has been exposed , one suggests that the pedagogical proposal be measured anew for a better articulation of the game usage with different trends in math education